Platelet ITAM signaling is critical for vascular integrity in inflammation - Boulaftali, Yacine (American Society for Clinical Investigation, 2013)
Platelets play a critical role in maintaining vascular integrity during inflammation, but little is known about the underlying molecular mechanisms. Here we report that platelet immunoreceptor tyrosine activation motif (ITAM) signaling, but not GPCR signaling, is critical for the prevention of inflammation-induced hemorrhage. To generate mice with partial or complete defects in these signaling pathways, we developed a protocol for adoptive transfer of genetically and/or chemically inhibited platelets into thrombocytopenic (TP) mice. Unexpectedly, platelets with impaired GPCR signaling, a crucial component of platelet plug formation and hemostasis, were indistinguishable from WT platelets in their ability to prevent hemorrhage at sites of inflammation. In contrast, inhibition of GPVI or genetic deletion of Clec2, the only ITAM receptors expressed on mouse platelets, significantly reduced the ability of platelets to prevent inflammation-induced hemorrhage. Moreover, transfusion of platelets without ITAM receptor function or platelets lacking the adapter protein SLP-76 into TP mice had no significant effect on vascular integrity during inflammation. These results indicate that the control of vascular integrity is a major function of immune-type receptors in platelets, highlighting a potential clinical complication of novel antithrombotic agents directed toward the ITAM signaling pathway.